The Effect of Artificial Substrate and Carbon Source Addition on Bacterial Diversity and Community Composition in Water in a Pond Polyculture System - Kun Guo; Mumin Shi; Xiaoli Huang; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Guoliang Ruan; Zhigang Zhao (Fishes, 2024)
The use of artificial substrates and biofloc technology can favor fish culture and improve water quality. The aim of this study was to evaluate whether artificial substrates and carbon source additions modify the microbial activity of water bodies. The diversity and structure of microflora in the water after adding artificial substrates and carbon sources to the ponds were analyzed using high-throughput sequencing based on the V3-V4 region of 16S rRNA genes. The results showed that there was no difference in the richness and diversity of intestinal microflora between the control and experimental groups. Principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) showed that artificial substrate and carbon source addition changed the structure of the microflora. The results of a linear discriminant analysis (LDA) effect size (LefSe) indicated 11 biomarkers in the EGˍst group. Spearman correlation heatmap analysis showed that environmental factors affected the bacterial communities, and the results of a redundancy analysis indicated that chemical oxygen demand was a critical factor in controlling the bacterial communities in the water. These results provide an understanding of the effect of artificial substrate and carbon source addition on bacterial diversity and community composition in water.

Three Types of Enteromorpha prolifera Bio-Products Based on Different Processing Procedures as Feed Additives in the Diets of Pacific White Shrimp (Litopenaeus vannamei) - Zhibin Zhou; Lubo Wang; Mingqin Dai; Qingyan Gao; Peng Wang; Lili Zhao; Yanlu Li; Rui Xi; Mingchao Pan; Qiang Ma; Houguo Xu; Mengqing Liang; et al. (Fishes, 2023)
A feeding trial was conducted to evaluate the biological activities of Enteromorpha prolifera bio-products in the diets of Pacific white shrimp (Litopenaeus vannamei). Bio-products of E. prolifera included E. prolifera meal, E. prolifera hydrolysate and E. prolifera polysaccharide, which was supplied using different processing procedures. The control diet was supplemented without any E. prolifera bio-products or dietary attractants. Experimental diets were formulated to contain 0.2% and 0.4% of E. prolifera hydrolysate (EPH0.2% and EPH0.4%), 0.03% of E. prolifera polysaccharide (EPP0.03%), 3% of E. prolifera meal (EPM3%), 0.1% of dimethyl-β-propiothetn (DMPT0.1%) and 1% of squid paste (SP1%). Shrimp (~8 g) were randomly distributed in 21 tanks and fed for 44 days. Feed intake showed that 3% of E. prolifera meal and 0.4% of E. prolifera hydrolysate in diets exhibited similar attractant effects as 0.1% of DMPT. Gross qualitative observation showed that the abundance of lipid droplets decreased in hepatopancreas of the EPH0.4% and EPM3% groups, which were supported by hepatopancreas triacylglycerol (TG), where significantly lower concentrations were observed in the EPH0.4% and EPM3% groups compared with the control group. Similarly, TG and low-density lipoprotein cholesterol in serum significantly decreased in the EPH0.4%, EPP0.03% and EPM3% groups compared to the control group. Supplemental E. prolifera bio-products resulted in significantly higher serum glutathione level of EPP0.03% or superoxide dismutase activities of EPH0.4% and EPM3%, but significantly lower serum malondialdehyde level of EPM3%. In addition, tnf-α expression in hepatopancreas was significantly down-regulated in shrimp fed the EPH0.2%, EPH0.4% and EPM3% diets. Based on survival analysis, E. prolifera bio-products improved the resistance of shrimp to hypoxic stresses. Thus, this study confirmed that bio-products of E. prolifera supplied using different processing procedures could be used to reduce the amount of E. prolifera in feed of shrimp without compromising their biological functions.

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Combined Effects of Eco-Substrate and Carbon Addition on Water Quality, Fish Performance and Nutrient Budgets in the Pond Polyculture System - Kun Guo; Zhigang Zhao; Jun Xie; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Xiaoli Huang (Fishes, 2022)
Traditional aquaculture can cause serious environmental pollution. Biofilm and biofloc technology have the potential to limit aquaculture pollution. An outdoor experiment was conducted to evaluate the combined effects of eco-substrates and carbon addition on water quality, fish performance and nutrient budgets in the pond polyculture system. In the treatment group, the total ammonia nitrogen, nitrate nitrogen, nitrite nitrogen, and total nitrogen of the water were significantly lower compared to the control group (p 92%) and P (>95%) input during the experiment. Comprehensive accumulation was the main N (>58%) and P (>69%) output. The N and P feed input and comprehensive accumulation output declined in the treatment group. The N utilization efficiency in the experimental group increased slightly (p > 0.05), while the P utilization efficiency in the experimental group was significantly higher compared to the control (p

Population Genetic Diversity and Differentiation of Mitten Crab, Genus Eriocheir, Based on Microsatellite Markers - Shihui Wang; Liang Luo; Rui Zhang; Kun Guo; Wei Xu; Zhigang Zhao (Fishes, 2022)
Mitten crab, Eriocheir sensu stricto, is an important indigenous aquatic species and food source in Eastern Asia. Genetic diversity is an important prerequisite for the conservation and utilization of germplasm resources. However, the genetic diversity and differentiation of Eriocheir s. s. remains unclear. This study evaluated population genetic diversity and genetic differentiation of three Eriocheir s. s. populations from Suifenhe (SFH), Liaohe (LH), and Nanliujiang (NLJ), China, based on 19 microsatellite markers. The mean observed number of alleles (Na) was 22.84 alleles, and the mean polymorphism information content (PIC) was 0.86, which demonstrated high genetic diversity. The allele frequency distribution showed an “L” shape, ranging from 0.01 to 0.74. The genetic diversity parameter values of the LH population were higher than those of the other two populations. All pairwise FST values showed significant differences among the three Eriocheir s. s. populations (p